If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 6(v + 2) + -3v Reorder the terms: -3 = 6(2 + v) + -3v -3 = (2 * 6 + v * 6) + -3v -3 = (12 + 6v) + -3v Combine like terms: 6v + -3v = 3v -3 = 12 + 3v Solving -3 = 12 + 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. -3 + -3v = 12 + 3v + -3v Combine like terms: 3v + -3v = 0 -3 + -3v = 12 + 0 -3 + -3v = 12 Add '3' to each side of the equation. -3 + 3 + -3v = 12 + 3 Combine like terms: -3 + 3 = 0 0 + -3v = 12 + 3 -3v = 12 + 3 Combine like terms: 12 + 3 = 15 -3v = 15 Divide each side by '-3'. v = -5 Simplifying v = -5
| w+l-2.8l=4.3 | | f(3)=-2(3) | | 50h+100=x | | 4-x^2+16y^2=0 | | 2x^2-3=197 | | -3(2x-2)=45+3 | | 6x^3+21x^2-45x= | | 64=4xf | | 3x+19*5=2 | | 2(y-6)=12 | | (w)(w+2)=40 | | 10x^4-9x^3= | | b+23.19=38.72 | | 3y+4=x+14 | | e^3x=87 | | 5(3a+2)=12a+11 | | 25+x^2=225 | | (5w)*(5w+18)=-81 | | 0=x^3+64 | | -8+6n=-50 | | 7xv=28 | | -8n-1=15 | | x+3.6=-7.1 | | 4x-12.5=3.8 | | F(x)=-16x(2)+64x | | 5m+1=1 | | s-4.70=4.75 | | 7j+2=9j-4 | | f(x)=25000(1*.20)x | | -11c= | | -5.8+3.2x+1x^2=0 | | 8+7n=15 |